Analysis of nutrition and functional ingredients of fermented Codonopsis pilosula Huangjiu - WANG Nan, GAO Yingrui, XU Qiaohong, HU Fangdi (Zhongguo niangzao, 2024)
In this study, fermented Codonopsis pilosula Huangjiu (FCHJ) was prepared using fermented C. pilosula as raw material, and C. pilosula Huangjiu (CHJ) as the control, the contents of total phenols, total flavonoids and amino acids, mineral elements and antioxidant activity in vitro were determined. The immunomodulatory activities of fermented C. pilosula Huangjiu polysaccharide (FCHJ-CP) in vitro were studied by mouse spleen lymphocyte proliferation experiments, proliferation and phagocytosis of RAW264.7 cells and NO release. The results showed that the contents of total phenols and total flavonoids in FCHJ increased by 32.53% and 60.79% compared with the control. 17 kinds of amino acids were detected by FCHJ, including 8 kinds of essential amino acids, which accounted for 35.53% of the total amino acids. The two kinds of samples were rich in nutrition and good in taste, both were rich in essential mineral elements such as K, Ca, Na, Mg, Fe, Zn and other essential mineral elements. The maximum scavenging rates of FCHJ on 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH), superoxide anion and hydroxyl radical were 97%, 98%, 100%, respectively. When the mass concentration of FCHJ-CP was 200 μg/ml, it could significantly promote the proliferation of mouse spleen lymphocytes (P<0.05), significantly promote the proliferation and phagocytosis of RAW264.7 cells and promote the release of NO (P<0.01).